Emerging evidence of seed transmission of begomoviruses: implications in global circulation and disease outbreak - Sandra, Nagamani; Mandal, Bikash (Frontiers in Plant Science, 2024)
Begomoviruses (family Geminiviridae) are known for causing devastating diseases in fruit, fibre, pulse and vegetable crops throughout the world. Begomoviruses are transmitted in the field exclusively through insect vector whitefly (Bemisia tabaci) and the frequent outbreaks of begomoviruses are attributed largely due to the abundance of whitefly in the agriecosystem. Begomoviruses being phloem-borne were known not be transmitted through seeds of the infected plants. The recent findings of seed transmission of begomoviruses brought out a new dimension of begomovirus perpetuation and dissemination. The first convincing evidence of seed transmission of begomoviruses was known in 2015 for sweet potato leaf curl virus followed by several begomoviruses, like bhendi yellow vein mosaic virus, bitter gourd yellow mosaic virus, dolichos yellow mosaic virus, mungbean yellow mosaic virus, mungbean yellow mosaic India virus, pepper yellow leaf curl Indonesia virus, tomato leaf curl New Delhi virus, tomato yellow leaf curl virus, tomato yellow leaf curl Sardinia virus and okra yellow mosaic Mexico virus. These studies brought out two perspectives of seed-borne nature of begomoviruses: (i) presence of begomovirus in the seed tissues derived from the infected plants but no expression of disease symptoms in the progeny seedlings and (ii) the seed infection successfully transmitted the virus to cause disease to the progeny seedlings. It seems that the seed transmission of begomovirus is a feature of a specific combination of host-genotype and virus-strain, rather than a universal phenomenon. This review comprehensively describes the seed transmitted begomoviruses reported in the last 9 years and the possible mechanism of seed transmission. An emphasis is placed on the experimental results that proved the seed transmission of various begomoviruses, factors affecting seed transmission and impact of begomovirus seed transmission on virus circulation, outbreak of the disease and management strategies.